Effect of bacterial amylase pretreatment on bioethanol production from starch-based solid waste (SBSW). Issue 17 (1st September 2016) - Kumar, Vinod; Nanda, Manisha; Singh, Ajay
ABSTRACT: Fuels derived from biomass are essential in order to overcome the excessive dependence on petroleum. They also minimize the emissions of greenhouse gases. Pretreatment in biofuel production is a very important step. Pretreatment is not only costly in its own right but also has a pervasive impact on the cost of virtually all other processing operations. The present study investigates the effect of bacterial amylase pretreatment on ethanol production from different kinds of starch-based solid waste (SBSW). For this purpose four amylase-producing bacterial isolates were obtained from samples collected from municipal waste dumping sites. The isolated bacteria were then used for the pretreatment of SBSW for ethanol production. After bacterial amylase pretreatment, 13% yield of ethanol was obtained.